MWA and VLA Observations of Diffuse Radio Lobes in M87 - Linhui Wu; Fu-Guo Xie; Qian Zheng; Quan Guo; Huanyuan Shan; Dan Hu; Stefan W. Duchesne; Nick Seymour; Jingying Wang; Junhua Gu; Qingwen Wu; Zhenghao Zhu; et al. (The Astrophysical Journal)
This study investigates the projected, quasi-symmetric ∼46 kiloparsec-scale diffuse radio lobes surrounding the giant elliptical galaxy M87, utilizing well-sampled wideband (60 MHz–10.55 GHz) observations from the Murchison Widefield Array and Very Large Array, supplemented by data from the Low-frequency Array and Effelsberg. The observed structures feature sharp edges and filaments, with nearly uniform and moderately steep spectral indices ( α , mostly within −1.2 ≤ α ≤ −0.8), indicating turbulence. Well-sampled radio spectra for the lobes’ diffuse region are derived using the continuous injection (CI) model (with α _inj  ≃ −0.86 and ν _b  ≃ 1.72 GHz), and for its three localized regions using the impulsive injection model (e.g., the Jaffe–Perola (JP) model). From energy equipartition analysis, we estimate the typical magnetic field strength in the lobes’ diffuse region to be B _eq  ≃ 10 μ G. The age of the lobes is estimated as ∼30–50 Myr, based on lifetimes derived from the CI and JP models and sound crossing time. Outflow powers of ∼(0.2–2) × 10 ^44 erg s ^–1 for the lobes’ diffuse components and ∼(1–11) × 10 ^44 erg s ^–1 for the whole source are calculated. With this power assessment, we conclude that the galactic stellar wind has a negligible effect, and the active galactic nucleus (AGN)-driven jet can provide the necessary energy for the whole system. Furthermore, we argue that while the wind driven by current AGN activity is unlikely to power the lobes’ diffuse components, an average enhancement of AGN activity by a factor of ∼10 ^2 over the past ∼30–50 Myr remains plausible.